2018
DOI: 10.3389/fonc.2018.00561
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of IL-33 to the Pathogenesis of Colorectal Cancer

Abstract: The development of colorectal cancer (CRC) is not only determined by transformed cells per se, but also by factors existing in their immune microenvironment. Accumulating scientific evidence has revealed that interleukin (IL)-33, an IL-1 family member, plays an essential role in the regulation of immune response and is relevant in CRC pathogenesis. Data from both human and experimental studies demonstrated that IL-33 inhibits host anti-tumor immunity, remodels tumor stroma and enhances angiogenesis, thereby pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 90 publications
1
19
0
Order By: Relevance
“…Previous studies confirmed important role of IL-33 in CRC pathogenesis 13,14 . It is known that IL-33 activates core stem cell genes, recruits macrophages into the cancer microenvironment and stimulates them to produce prostaglandin E2, which all promote carcinogenesis of CRC and metastasis of cancers 16,30 .…”
Section: Figure 4 Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies confirmed important role of IL-33 in CRC pathogenesis 13,14 . It is known that IL-33 activates core stem cell genes, recruits macrophages into the cancer microenvironment and stimulates them to produce prostaglandin E2, which all promote carcinogenesis of CRC and metastasis of cancers 16,30 .…”
Section: Figure 4 Discussionsupporting
confidence: 56%
“…Interleukin (IL)-33, an IL-1 family member, plays an essential role in the regulation of immune response after cellular stress or damage 13,14 . Recent study revealed that IL-33 by biding to its receptor ST2 inhibits host anti-tumor immunity, remodels tumor stroma and enhances angiogenesis, thereby promoting the development of CRC 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, host anti-tumor immunity is regulated by a complex immune cellular network in patents with CRC (1,3,70,(91)(92)(93). For instance, a number of recent studies have reported that diverse TH subsets TH9, TH17 and TH22 and their main cytokines such as IL-9, IL-17 and IL-22 participate in the modulation of immune response in patients with CRC (91).…”
Section: The Possible Mechanisms Leading To a Distinct Therapeutic Efmentioning
confidence: 99%
“…Unfortunately, metastasis is often observed at the time of diagnosis, and curative surgical resection becomes impossible in these patients. Thus, to improve the prognosis of metastatic CRC (mCRC) patients, many researchers have investigated the escape immunosurveillance mechanisms by which the CRC progresses and metastases persistently (1)(2)(3)(4). A growing body of evidence from various studies has demonstrated that immune checkpoints are negative regulators for host anti-tumor immune function and could significantly suppress the host anti-tumor immune reactivity (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Although controversial, evidence points out an important role of the alarmin IL-33 in intestinal tumorigenesis [ 114 ]. IL-33 is elevated in CRC, both in tissue and serum samples, and the IL-33/ST2L axis shapes immune cell populations in the tumor, promoting the accumulation or depletion of immunosuppressive and anti-tumorigenic cells, respectively [ 115 , 116 ]. Moreover, the IL-33/ST2L axis is critical for Treg expansion and, therefore, it could indirectly promote tumor suppression.…”
Section: Type 2 Immunity Responses In the Context Of Colorectal Camentioning
confidence: 99%